2019
DOI: 10.1186/s42490-019-0001-4
|View full text |Cite
|
Sign up to set email alerts
|

Robotic and laparoscopic surgery of the pancreas: an historical review

Abstract: Surgery of the pancreas is a relatively new field, with operative series appearing only in the last 50 years. Surgery of the pancreas is technically challenging. The entire field of general surgery changed radically in 1987 with the introduction of the laparoscopic cholecystectomy. Minimally Invasive surgical techniques rapidly became utilized worldwide for gallbladder surgery and were then adapted to other abdominal operations. These techniques are used regularly for surgery of the pancreas including distal p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 52 publications
0
23
0
1
Order By: Relevance
“…1,2 This has resulted in numerous case-series and registry studies on minimally invasive distal pancreatectomy (MIDP) and minimally invasive pancreatoduodenectomy (MIPD). [3][4][5][6][7][8][9][10][11] These studies reported less intraoperative blood loss, lower morbidity, and shorter hospital stay after MIPR (compared with the conventional open approach). However, there were also some concerns caused by high conversion rates, inferior oncological outcomes, and increased mortality reported in low-volume centers; these concerns hampered further widespread introduction of MIDP and MIPD.…”
mentioning
confidence: 96%
“…1,2 This has resulted in numerous case-series and registry studies on minimally invasive distal pancreatectomy (MIDP) and minimally invasive pancreatoduodenectomy (MIPD). [3][4][5][6][7][8][9][10][11] These studies reported less intraoperative blood loss, lower morbidity, and shorter hospital stay after MIPR (compared with the conventional open approach). However, there were also some concerns caused by high conversion rates, inferior oncological outcomes, and increased mortality reported in low-volume centers; these concerns hampered further widespread introduction of MIDP and MIPD.…”
mentioning
confidence: 96%
“…Training in robotic surgery is emphasized in contrast to what happened when laparoscopic surgery was introduced. 2 Simulators designed for robotic-assisted surgery training are generally high-fidelity, large and expensive because they closely resemble the actual daVinci robotic-assisted surgical system robot (Intuitive, Sunnyvale CA) which is the most commonly used system. A reasonably low-cost portable VR trainer for the daVinci system was recently described.…”
Section: Discussionmentioning
confidence: 99%
“…1 Laparoscopic surgery training in the late 1980s and early 1990s often proceeded without verification of skills or competency. 2 Since that time, training to perform procedures has undergone widespread change and simulation has become an important component. Selecting the optimal simulator for a specific procedure and trainee group is difficult.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that patients with benign disease were hospitalized for 5 days after major Although laparoscopic hepatectomy is widely used in most HPB centers, especially in atypical or wedge resection, laparoscopic techniques are not applied at the same speed in pancreatectomy. In particular, the application of laparoscopic surgery in complex operations such as pancreaticoduodenectomy, even in the leading institutions of robotic surgery, has not shown an improvement in length of hospitalization or morbidity, which needs further data to demonstrate [31,32].…”
Section: Eras and Endoscopymentioning
confidence: 99%